2014
DOI: 10.3389/fpls.2014.00140
|View full text |Cite
|
Sign up to set email alerts
|

An update: improvements in imaging perfluorocarbon-mounted plant leaves with implications for studies of plant pathology, physiology, development and cell biology

Abstract: Plant leaves are optically complex, which makes them difficult to image by light microscopy. Careful sample preparation is therefore required to enable researchers to maximize the information gained from advances in fluorescent protein labeling, cell dyes and innovations in microscope technologies and techniques. We have previously shown that mounting leaves in the non-toxic, non-fluorescent perfluorocarbon (PFC), perfluorodecalin (PFD) enhances the optical properties of the leaf with minimal impact on physiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
50
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 30 publications
0
50
0
Order By: Relevance
“…This may hamper the visualization of the subcellular architecture of plant samples not adequately coated by the observation medium. It can be avoided by mounting plants in an oxygen-saturated perfluorocarbon (Littlejohn et al, 2010(Littlejohn et al, , 2014Littlejohn and Love, 2012;Chi and Ambrose, 2016). SIM also is prone to optical artifacts that may be caused by inaccurate grid movements (Langhorst et al, 2009), and resolving capacity depends on the labeling quality and the signal-to-noise ratio (SNR) of the sample.…”
Section: Simmentioning
confidence: 99%
“…This may hamper the visualization of the subcellular architecture of plant samples not adequately coated by the observation medium. It can be avoided by mounting plants in an oxygen-saturated perfluorocarbon (Littlejohn et al, 2010(Littlejohn et al, , 2014Littlejohn and Love, 2012;Chi and Ambrose, 2016). SIM also is prone to optical artifacts that may be caused by inaccurate grid movements (Langhorst et al, 2009), and resolving capacity depends on the labeling quality and the signal-to-noise ratio (SNR) of the sample.…”
Section: Simmentioning
confidence: 99%
“…() and Littlejohn et al . (). To maximise IR transmission, the standard galvanometer scanning mirrors were replaced with silver galvanometric mirrors, the tube lens was replaced with a MgF 2 coated lens and the confocal dichroic was replaced by a silver mirror with high reflectivity throughout the visible and NIR (21010, Chroma Technologies, USA).…”
mentioning
confidence: 97%
“…Fresh, excised plant leaves were mounted in perfluorodecalin (Littlejohn et al, 2010) prior to imaging, which has been shown not to interfere with Raman-based imaging in plants (Mansfield et al, 2013;Littlejohn et al, 2014).…”
Section: Srs Microscopymentioning
confidence: 99%